Investigation of epigenetic factors TET1-3 and PRC2 in spermatogenesis and mature spermatozoa: role in male infertility - Shiplu, Shanjid Ahmed; Justus Liebig University Giessen (My University, 2024)
This study investigated the role of aberrant epigenetic mechanisms in spermatogenesis and male infertility. We examined the expressions and retention of TET1, PRC2 components, and H3K27me3 during human and mouse spermatogenesis and the mRNA and methylation levels of their target genes in mature human sperm from fertile and infertile/subfertile men. We first studied the impact of Tet1 knockout on PRC2 and H3K27me3 and its implications for male fertility. In Tet1-deficient mice, Eed was absent, and Ezh2 and Suz12 expressions shifted to early and late stages of spermatogenesis respectively. As Eed knockout mice are infertile and Eed helps establish H3K27me3 through PRC2, and this mark is passed from sperm to the next generation, these results and altered H3K27me3 expression suggest Tet1's indirect role in male infertility. Next, we examined the retention of TET1, H3K27me3, and PRC2 components at the protein level in human motile spermatozoa. In patients’ spermatozoa, we found aberrant retention of H3K27me3 and a trend of higher enrichment of H3K27me3 in selected genes of developmental relevance (GDR). Further analysis revealed dysregulation of TETs, PRC2 components and selected GDR in subfertile patients. Particularly, TET1, TET3, SOX1-2, and OCT4 mRNA levels were significantly upregulated in subfertile patients. Additionally, patients exhibited significantly lower mRNA levels of EED, FOXA2, HERV-w and dysregulated promoter methylation levels of EZH2, SUZ12 and GATA2. Our data suggest that high TET1 and TET3 mRNA levels and over-retention of H3K27me3 are characteristics of infertile patients. These aberrations were linked with the overexpression and hypomethylation of a few GDR in spermatozoa. As the affected GDR code transcription factors, which are critical for embryonic genome activation (EGA) and preimplantation embryogenesis, sperm-inherited RNA and proteins may play a crucial role in early embryonic development, i.e. their aberrations may impact embryo development, implantation, and cause unsuccessful pregnancy. In conclusion, our study has established a preliminary link between TETs, PRC2, H3K27me3 and GDR, and suggest that their interplay is important for governing EGA and embryogenesis, and herewith also for male fertility.
Keywords: ddc:610